Odpowiedź :
Odpowiedź:
zad 10
a² - b² = 36
a - b = 4
a²- b² = (a - b)(a + b) = 36
4(a + b) = 36 | : 4
a + b = 36/4= 9
układ równań
a + b = 9
a - b = 4
dodajemy równania
a + a + b - b = 9 + 4
2a = 13
a = 13/2 = 6,5
a + b = 9
6,5 + b = 9
b = 9 - 6,5 = 2,5
sprawdzenie:
a² - b² = 36
6,5²- 2,5² =36
42,25 - 6,25 = 36
36 = 36
L = P
zad 11
a₁ = x
a₂ = x + 3
a₃ = 3x + 5
a₃ - a₂ = a₂ - a₁
3x + 5 - (x+ 3) = x + 3 - x
3x + 5 - x - 3 = 3
2x+ 2 = 3
2x = 3 - 2 = 1
x = 1/2 = 0,5
sprawdzenie
a₁ = 0,5
a₂ = 0,5 + 3 = 3,5
a₃ = 3 * 0,5 + 5 = 1,5 + 5 = 6,5
a₃ - a₂ = a₂ - a₁
6,5 - 3,5 = 3,5 - 0,5
3 = 3
L = P